Innovative structural systems for industrial buildings using fiber reinforced concrete and material nonlinear FEM-Based models - Barros, Joaquim A. O. (2009)
Fibre Reinforced Concrete (FRC) can be very effective in precast pre-stressed high strength concrete structures, since shear reinforcement and passive longitudinal bars can be totally replaced by fibre reinforcement. To simulate adequately the fibre reinforcement benefits, material constitutive models, able of capturing the crack initiation and crack propagation need to be used, under the frame-work of FEM-based analysis. In the present work, the use of FRC was explored for the development of innovative structural systems for industrial buildings. The connections between structural precast elements were also simulated. The numerical simulations are described and the results are analyzed and discussed.